2013
DOI: 10.3171/2013.5.spine121067
|View full text |Cite
|
Sign up to set email alerts
|

A standardized nomenclature for cervical spine soft-tissue release and osteotomy for deformity correction

Abstract: Object Cervical spine osteotomies are powerful techniques to correct rigid cervical spine deformity. Many variations exist, however, and there is no current standardized system with which to describe and classify cervical osteotomies. This complicates the ability to compare outcomes across procedures and studies. The authors' objective was to establish a universal nomenclature for cervical spine osteotomies to provide a common language among spine surgeons. Methods A proposed nomenclature with 7 anatomical gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 60 publications
0
78
0
1
Order By: Relevance
“…Therefore, our data suggest that the clinical advantages from surgical intervention were not affected by the location of the osteotomy. Our observed clinical benefits may be due to improvements in radiographic parameters of cervical alignment [19,20]. Cervical SVA directly correlates with NDI and SF-36 PCS scores [21,22].…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, our data suggest that the clinical advantages from surgical intervention were not affected by the location of the osteotomy. Our observed clinical benefits may be due to improvements in radiographic parameters of cervical alignment [19,20]. Cervical SVA directly correlates with NDI and SF-36 PCS scores [21,22].…”
Section: Discussionmentioning
confidence: 79%
“…A reliability analysis demonstrated that this system is consistent and directly applicable. 4 As an initial step toward the long-term goal of developing a comprehensive classification for CSD, our objectives in the present study were to propose and validate an initial classification system for CSD that will have utility in reporting of treatment options and outcomes for affected patients.…”
mentioning
confidence: 99%
“…46,49 In addition, Ames et al recently reported a standardized nomenclature for cervical spine soft-tissue release and osteotomy for deformity correction. 4 The proposed nomenclature includes 7 anatomical grades of increased extent of bone/soft tissue resection and destabilization, as well as a surgical approach modifier. A reliability analysis demonstrated that this system is consistent and directly applicable.…”
mentioning
confidence: 99%
“…With a posterior approach, particularly a combined anteroposterior approach, variations of posteriorly based osteotomies were used. 3 While osteotomies are extremely powerful techniques, they are not ideal in patients with mainly anterior thecal sac compression who do not require posterior fusion or in patients who cannot tolerate a prone position. Therefore, utilizing an anterior approach to cervical kyphosis correction may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, anterior decompression and spinal column reconstruction are not easily achieved via a posterior-only approach in the cervical spine, and a combined anteroposterior procedure is commonly needed when treating cervical deformity caused by an anterior element pathology. 3 A technique that allows direct access to anterior pathology, adequate decompression, and various extents of cervical kyphosis correction is ideal.…”
mentioning
confidence: 99%